EVALUASI PROGRAM SEKOLAH ADIWIYATA DI KOMPLEKS UPT SPF SDN BAWAKARAENG KOTA MAKASSAR - Kurniati; Baso Intang Sappaile; Patahuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to evaluate Context implementation of the Adiwiyata Program, Input for program implementation, implementation process and supporting and inhibiting factors, and product from program implementation. This research is evaluative with a qualitative approach using the CIPP evaluation model. Data collection was carried out through interviews, observation and document study. Data analysis techniques include collection, reduction, data presentation, and verification, with validation using triangulation and cross-check. The research results show that in aspects Context, There is a need for schools to create a clean, green and comfortable environment, which encourages school participation in the Adiwiyata Program. In aspect Input, the availability of human resources, budget, infrastructure, and program design supports program implementation in schools. In aspect Process, the program has been running according to Adiwiyata guidelines, although there are still challenges in increasing the involvement of all school members. Meanwhile, on aspects Product, The Adiwiyata program has contributed to the formation of an environmentally caring character in schools, although there are still aspects that need to be improved to achieve program sustainability. Factors supporting the success of the program include policy support, involvement of competent human resources, school commitment, budget, and availability of facilities and infrastructure. Meanwhile, inhibiting factors include the lack of individual awareness in protecting the environment and limited active participation from all school members. This research recommends that schools continue to increase the participation of all school members through intensive mentoring and encourage the role of the Makassar City Environmental Service (DLH) to be more active in supporting the sustainability of the Adiwiyata Program at the SDN Bawakaraeng UPT Complex. Keywords: Program Evaluation, Adiwiyata School, CIPP